How do International Financial Flows to Developing Countries Respond to Natural Disasters? - David, Antonio (Washington, D.C. : International Monetary Fund, 2010)
This paper uses multivariate dynamic panel analysis to examine the response of international financial flows to natural disasters. The models estimated for a large sample of developing countries point to differentiated responses of specific types of financial flows. The results show that remittance inflows increase significantly in response to shocks to both climatic and geological disasters. The models suggest a nuanced role for foreign aid. While the responses of aid flows to natural disaster shocks in general tend not to be statistically significant, international assistance to low income countries increases following geological disaster shocks. Furthermore, the results show that typically, other private capital flows (bank lending and equity) do not attenuate the effects of disasters and in some specifications, even amplify the negative economic effects of these events. The conclusions of the paper have implications for capital/financial account management policies. In particular, countries should take their vulnerability to natural disasters into account when considering the costs and benefits of the liberalization of private capital flows.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet